Communication Strategies of Islamic Education Teachers in Instilling Islamic Values in Fourth-Grade Students at SDN 2 Bugi, Sorawolio District, Baubau City - Fitriani, Fitriani; Basri, Basri; Yahya, Safaruddin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the communication strategies employed by Islamic Education teachers in instilling Islamic values in fourth-grade students at SD Negeri 2 Bugi. The need for effective communication strategies arises from the observed low application of Islamic values among students, which manifests in less polite behavior, low discipline, and ineffective teacher-student interactions. To address this issue, the fourth-grade Islamic Education teacher utilizes various communication strategies during classroom learning. This research adopts a descriptive method with a qualitative approach. The data sources include one class teacher and fourth-grade students at SD Negeri 2 Bugi. Data collection was conducted during the Islamic Education learning process, with interviews carried out after class sessions. The study was conducted from January 24 to March 23, 2025. Data analysis techniques were used to interpret the findings and provide insights into the effectiveness of the teacher’s communication strategies in fostering Islamic values among students.